Inquiring value: the pragmatist turn in business ethics - Rydenfelt, Henrik (Journal of business ethics, 2025)
30 years ago, R. Edward Freeman levied an influential challenge against the "separation thesis", which maintains that ethical and business concerns are distinct and separable. However, achieving an integration of empirical and normative research continues to pose significant challenges. In this article, it is argued that the tradition of philosophical pragmatism offers a pathway to bridge this divide. While Freeman’s critique is rooted in pragmatism, it falls short of fully embracing the pragmatist turn as advocated by Charles S. Peirce and John Dewey, who extended the methodologies of empirical inquiry to ethical issues. Typically, this pragmatist turn has been sidelined due to the formidable objection that norms and values cannot be empirically confirmed nor disconfirmed. This objection is critically examined, arguing that it is largely based on conceptions of science associated with positivism and logical empiricism, effectively challenged by pragmatism. Embracing a pragmatist perspective, it is argued, can substantially enhance both theoretical and empirical research within business ethics. This approach entails integrating observations that pertain to the values, norms and responsibilities of businesses. Conversely, with a comprehensive understanding of the theoretical underpinnings of such proposals, observations can help determine which ethical theories and perspectives best accommodate empirical findings. Additionally, pragmatism presents a novel approach to the role of business in society, enabling businesses to engage in democratic processes of inquiry into value.